Correlation between computed tomography imaging and histopathology in pleomorphic adenoma of parotid gland. Issue 4 (August 2018) - Kim, Heejin; Kim, So Young; Kim, Yoon-Joong; Ko, Jae-mun; Park, Min Ji; Kim, Ji Hoon; Hah, J. Hun; Kwon, Tack-Kyun; Kim, Kwang Hyun; Sung, Myung-Whun
Abstract: Objective: The purpose of this study was to correlate the CT imaging features and histopathological findings of pleomorphic adenomas (PA), and also try to identify its clinical significance. Methods: Totally 262 PAs in the parotid gland including 18 recurrent cases were retrospectively reviewed with preoperative CT and pathologic slides. Each pathologic slide was reviewed by two pathologists to calculate mean value of epithelial/mesenchymal component, and the results were correlated with features of CT scans. Results: PAs showing high contrast enhancement were correlated with high proportion of epithelial components in histopathologic findings. PAs with smooth border tend to have high proportion of epithelial components. The margin on CT imaging did not consisted with pathologic margin of resected specimens. In recurrent PAs, there was a significant difference on CT contrast enhancement, not in proportion of epithelial component. Conclusion: The histopathology and CT imaging features of PAs were variable, but we can find the correlation of epithelial component and CT contrast enhancement. Further large scale study would be expected to identify the clinical significance of CT imaging features and histopathologic findings of PAs.